La persona de Matthew McConaughey au début des années 2010 : masculinité, hétérosexualité et blanchité liquides - Maureen Lepers (Mise au Point)
This paper deals with the ambivalences contained within actor Matthew McConaughey’s persona in an intersectional perspective. Using the tools of gender studies, star studies and critical white studies, it looks at four parameters – gender, sexual orientation, class and race – in four of McConaughey’s characters of the last decade: Magic Mike’s stripper Dallas (Steven Soderbergh, 2012), Killer Joe’s killer Ward (William Friedkin, 2012), the lonesome Mud in the movie of the same name (Jeff Nichols, 2012), and Rust, True Detective’s tortured but brilliant detective. Released over a short period of time, these movies show how diverse McConaughey’s career has always been (from labelled independent films to Hollywood blockbusters and quality TV) and enable us to understand how masculinity, heterosexuality and whiteness work as interlocked systems. This paper first analyzes how McConaughey’s gender performance in Magic Mike works to shatter the sedimented heterosexual icon he used to embody in the romantic comedies of the 2000s. It then moves on to an examination of the way the actor’s body is constantly spectacled and eroticized, resulting in a confusing and unsteady representation of heterosexual masculinity. Finally, it shows how the questioning of McConaughey’s heterosexuality “makes his whiteness strange”, as Richard Dyer would put it.